Automated Synthesis and Initial Evaluation of (4′-Amino-5′,8′-difluoro-1′H-spiro[piperidine-4,2′-quinazolin]-1-yl)(4-[18F]fluorophenyl)methanone for PET/MR Imaging of Inducible Nitric Oxide Synthase - Skye Hsin-Hsien Yeh; Wen-Sheng Huang; Chuang-Hsin Chiu; Chuan-Lin Chen; Hui-Ting Chen; Dae Yoon Chi; Zhengxing Ge; Tsung-Hsun Yu; Pao-Yeh Wang; Yu-Yeh Kuo; Chun-Tse Hung; Geng-Ying Li; et al. (Molecular Imaging)
Background. Inducible nitric oxide synthase (iNOS) plays a crucial role in neuroinflammation, especially microglial activity, and may potentially represent a useful biomarker of neuroinflammation. In this study, we carefully defined a strategic plan to develop iNOS-targeted molecular PET imaging using (4′-amino-5′,8′-difluoro-1′H-spiro[piperidine-4,2′-quinazolin]-1-yl)(4-fluorophenyl)methanone ([18F]FBAT) as a tracer in a mouse model of lipopolysaccharide- (LPS-) induced brain inflammation. Methods. An in vitro model, murine microglial BV2 cell line, was used to assess the uptake of [18F]FBAT in response to iNOS induction at the cellular level. In vivo whole-body dynamic PET/MR imaging was acquired in LPS-treated (5 mg/kg) and control mice. Standard uptake value (SUV), total volume of distribution (Vt), and area under the curve (AUC) based on the [18F]FBAT PET signals were determined. The expression of iNOS was confirmed by immunohistochemistry (IHC) of brain tissues. Results. At the end of synthesis, the yield of [18F]FBAT was 2.2–3.1% (EOS), radiochemical purity was >99%, and molar radioactivity was 125–137 GBq/μmol. In vitro, [18F]FBAT rapidly and progressively accumulated in murine microglial BV2 cells exposed to LPS; however, [18F]FBAT accumulation was inhibited by aminoguanidine, a selective iNOS inhibitor. In vivo biodistribution studies of [18F]FBAT showed a significant increase in the liver and kidney on LPS-treated mice. At 3 h postinjection of LPS, in vivo, the [18F]FBAT accumulation ratios at 30 min post intravenous (i.v.) radiotracer injection for the whole brain, cortex, cerebellum, and brainstem were 2.16±0.18, 1.53±0.25, 1.41±0.21, and 1.90±0.12, respectively, compared to those of mice not injected with LPS. The mean area under the curve (AUC0-30min), total volume of distribution (Vt, mL/cm3), and Ki (influx rate) of [18F]FBAT were 1.9±0.21- and 1.4±0.22-fold higher in the 3 h LPS group, respectively, than in the control group. In the pharmacokinetic two-compartment model, the whole brain Ki of [18F]FBAT was significantly higher in mice injected with LPS compared to the control group. Aminoguanidine, selective iNOS inhibitor, pretreatment significantly reduced the AUC0-30min and Vt values in LPS-induced mice. Quantitative analysis of immunohistochemically stained brain sections confirmed iNOS was preferentially upregulated in the cerebellum and cortex of mice injected with LPS. Conclusion. An automated robotic method was established for radiosynthesis of [18F]FBAT, and the preliminary in vitro and in vivo results demonstrated the feasibility of detecting iNOS activity/expression in LPS-treated neuroinflammation by noninvasive imaging with [18F]FBAT PET/MRI.